Utilization of carbonated and granulated steel slag aggregate in concrete. (1st June 2015) - Pang, Bo; Zhou, Zonghui; Xu, Hongxin
Highlights: The concrete aggregate is fully replaced by carbonated steel slag aggregate (CSA). Volume stability of concrete with CSA is satisfactory. The basic properties of concrete are improved by CSA. The results prove the possibility of using large number of steel slag as aggregate to instead of nature aggregate. Abstract: An experimental program was carried out to investigate the possibility of producing carbonated granulated steel slag aggregate (CSA) to replace common natural aggregate (NA) like limestone, quartzite, etc. and steel slag aggregate (SSA). Slump and compressive strength were tested to evaluate the fresh and hardened properties of concrete with different aggregate. Mineralogy, morphology, pore structure and volume stability properties of aggregate and concrete were analyzed. Test results showed that carbonation treatments can significantly improve the strength and volume stability of CSA and reduce water absorption, porosity and free calcium oxide. The workability of concrete with CSA was not significantly affected by the high water absorption of CSA. Besides, bleeding, and segregation were slighter and porosity of cement matrix was greatly reduced. After carbonation, harmful pores in aggregate reduced by 24.4% while harmless pores increased by 67.9%. The products were spindle and rod-like columnar calcium carbonate particles from SEM. Carbonation reduced the free CaO content from about 7 wt.% to less than 1 wt.% in 3 h. Compressive strength of concrete with CSA could be improved by 20% at 28 days. Strength of CSA concrete exceeded SSA concrete at 60 days. The volume stability of CSA met the required standards of autoclave chake and immersion expansion test.